Corrective feedback in teacher guides and SLA - Ellis, Rod (2013)
The kind of technical knowledge found in teacher guides is fundamentally different from the kind of technical knowledge found in published research about language learning. I refer to the former as ‘pedagogic discourse’ and to the latter as ‘research-based discourse’. The purpose of this article is to examine how links can be made between these two types of technical discourse. I will discuss two different ways. The first involves familiarizing teachers with what researchers have found out about L2 learning and then applying the findings to language pedagogy (i.e. SLA research  Language pedagogy). The second way is to start with commonly held views about how to teach (as reflected in the teacher guides) and then consider these in the light of how learners learn (i.e. Language pedagogy  SLA research). I will present arguments in favour of the second approach and illustrate it through an examination of commonly held pedagogic views about corrective feedback and the extent to which these are supported or questioned by what is known about corrective feedback in SLA.